1998
DOI: 10.1302/0301-620x.80b3.8013
|View full text |Cite
|
Sign up to set email alerts
|

MRI high-signal intensity in the menisci of asymptomatic children

Abstract: We reviewed retrospectively the MRI examinations of 108 knees of 80 children to identify the prevalence of a high signal in the menisci of those without symptoms. There were 51 boys and 29 girls with a mean age of 12.2 years (8 to 15). The prevalence of a high signal within the menisci was 66%, significantly higher than that in an adult group (29%). The prevalence decreased with age: grade-2 and grade-3 changes were observed in 80% of menisci at ten years of age, in 65% at 13 years and in 35% at 15 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Our observations concur with those of Hauger et al ( 24 ), where another potential cause of linear intermediate signal intensity in the meniscus was the presence of radially-oriented collagen tie fibers. However, abnormal high signal intensity in a linear distribution in the central layer of the meniscus can be caused by intrasubstance meniscal tears, increased vascularity ( 29 ), and meniscal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations concur with those of Hauger et al ( 24 ), where another potential cause of linear intermediate signal intensity in the meniscus was the presence of radially-oriented collagen tie fibers. However, abnormal high signal intensity in a linear distribution in the central layer of the meniscus can be caused by intrasubstance meniscal tears, increased vascularity ( 29 ), and meniscal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Also the change in MRI appearance of the meniscus seems to be a gradual process with the adolescent meniscus taking on more adult characteristics[5]. There is probably no specific age under which these criteria become unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…High signal within the meniscus has been demonstrated in 80% of asymptomatic menisci in 10 year olds, decreasing to 35% in 15 year olds[5]. One study of 51 children with suspected meniscal pathology found a sensitivity and specificity of 50% and 78% respectively for lateral meniscal tears in the under 15 age group.…”
Section: Introductionmentioning
confidence: 99%
“…Underlying degenerative changes, such as intrasubstance or myxoid degeneration in older patients and residual vascularity within the periphery of the meniscus in younger patients, can result in increased signal within the meniscus [10,11]. In the setting of trauma, increased signal within the meniscus can be secondary to meniscal contusion.…”
Section: Meniscimentioning
confidence: 99%